Radiobiology data of melanoma cells after low-energy neutron irradiation and boron compound administration. (September 2020) - Pedrosa-Rivera, María; Ruiz-Magaña, M. José; Álvarez, Patricia; Porras, Ignacio; Praena, Javier; Sabariego, Manuel P.; Köster, Ulli; Haertlein, Michael; Forsyth, V. Trevor; Soldner, Torsten; Ramírez, José C.; Jover, Clara; et al.
Abstract: The cold neutron beam at the PF1b line at the Institut Laue-Langevin (ILL), without fast neutrons and a low contribution of gamma rays, is a very suitable facility to measure cell damage following low-energy neutron irradiation. The biological damage associated with the thermal and the boron doses can be obtained in order to evaluate the relative biological effectiveness (RBE) for Boron Neutron Capture Therapy. Three different experiments were carried out on the A375 melanoma cell line: the first one in a hospital LINAC, to obtain the reference radiation data, and the other two at the ILL, in which the damage to cells with and without boron compounds added was measured. Highlights: The use of a very "clean" cold neutron beam for extracting radiobiology data of in-vitro samples is shown. The response of A375 melanoma cells from thermal neutrons and from the boron capture reaction with BPA have been obtained. The importance of accurate values of the radiobiology parameters for the reference photon irradiation has been pointed out.